Comparison of Glutathione, Cysteine, and Their Redox Potentials in the Plasma of Critically Ill and Healthy Children - Grunwell, Jocelyn R.; Gillespie, Scott E.; Ward, Janine M.; Fitzpatrick, Anne M.; Brown, Lou Ann; Gauthier, Theresa W.; Hebbar, Kiran B. (Frontiers in Pediatrics, 2015)
Background: Oxidative stress (OS) is known to play a role in critical illness due to an imbalance in reactive oxygen species (ROS) and reactive nitrogen species (RNS) and the body’s ability to detoxify pro-oxidants using small molecule anti-oxidants and anti-oxidant enzymes. Objective: To compare the concentrations of plasma redox metabolites and redox potentials for the Cys/CySS and GSH/GSSG thiol/disulfide pairs in critically ill children with healthy control children. Methods: We performed a prospective clinical observational study of children ages ≤ 18 years and weight ≥ 6 kg who were hospitalized between January 2010 and April 2012 in a 30 bed multidisciplinary medical-surgical pediatric intensive care unit (PICU). We measured the plasma concentrations of Cys, CySS, GSH, and GSSG within the first 24 hours of PICU arrival, and we calculated the redox potential for the Cys/CySS (Eh Cys/CySS) and GSH/GSSG (Eh GSH/GSSG) thiol/disulfide pairs in the plasma of 61 critically ill children and 16 healthy control children. Results: Critically ill children have less Cys (p = 0.009), less CySS (p = 0.011), less Total Cys ([Cys] + 2[CySS], p = 0.01), more GSSG (p < 0.001), and more oxidized Eh GSH/GSSG (p < 0.001) compared to healthy children. Conclusions: Our results demonstrate that in the presence of pediatric critical illness, the Total Cys/CySS thiol pool decreases while GSH is likely one component of the cellular redox system that reduces CySS back to Cys thus maintaining Eh Cys/CySS. The Total Cys pool is more abundant than the Total GSH pool in the plasma of children. Further investigation is needed to elucidate the differences in redox potentials in subgroups of critically ill children, and to determine whether differences in redox metabolite concentrations and redox potentials correlate with severity of critical illness and clinical outcomes.